The comparison of capnography and epigastric auscultation to assess the accuracy of nasogastric tube placement in intensive care unit patients - Elahe Heidarzadi; Rostam Jalali; Behzad Hemmatpoor; Nader Salari (BMC Gastroenterology, 2020)
Abstract Background Placement of nasogastric (NG) tubes is a common procedure for patients especially in intensive care units (ICUs). Thus, it is important to determine the correct placement of the tube to prevent misplacement in the airways. Accordingly, the aim of this study was to compare the epigastric auscultation and capnography in assessing the accuracy of NG tube insertion in ICU patients. Methods In this descriptive comparative study, 60 patients were selected trough convenience sampling. After insertion of the NG tube in a standard method, the accuracy of placement of the tube with both epigastric auscultation and capnography was investigated. The NG tube insertion accuracy was then confirmed via radiography. Data analysis was performed using statistical software SPSS version 23. Results The result showed that capnography had a sensitivity, specificity, and accuracy of 100, 92.5, and 95% respectively, but epigastric auscultation had 90, 80, and 83.4% respectively. The Kappa agreement coefficient between two methods was − 0.759. Conclusion The results revealed that the use of the capnography is preferable over the epigastric auscultation to confirm the correct insertion of the NG tube. It is recommended that more than one method be applied to detect and confirm the correct insertion of the NG tube.